(untitled) (Pulse, 2017)
Objective: This article serves to promote the interest of participants involved in management of hematological malignancies in the efficacy of flow cytometry in the immunophenotypic characterization of leukemias and lymphomas. This well-defmed characterization plays a crucial role in diagnosis, classification, prognostic evaluation, and detection of minimal residual disease, in the context of clinical features and morphological diagnosis. Methodology: Relevant literature was retrieved to highlight the principles of operation of flow cytometly, applications, derivable clinical information, sources of errors, necessary antibodies and general considerations towards definitive diagnosis of acute leukemia. Conclusion: Hematological malignancy is an extremely heterogeneous disorder. Use of flow cytometric immunophenotyping in these disorders is already proven over two decades and allowed clinicians for proper classification along the latest WHO classification guidelines and will pave the way for targeted therapy and better patient management. The flow cytometric immunophenotyping services in the country will significantly outweigh the cost by reducing the duration of hospital stay and patient management in right way. Pulse Vol.9 January-December 2016 p.27-36